Islamic Boarding School Challenges for Alpha Generation Student - Qiyadah Robbaniyah; Syaiful Anam (International journal of technology and education research, 2023)
Islamic boarding schools as Islamic educational institutions are serious in assisting the nation's children. So the researcher is interested in exploring the challenges of Islamic boarding schools for the alpha generation of students. With a place of research at the Islamic Center Bin Baz Islamic Boarding School in Yogyakarta. This research method is a qualitative method by collecting interview data, observation and documentation. The results of this study are; Generation Alpha is a term for people born in 2010 and after, this generation has advantages and characters that are different from the previous generation because they are very close to technology. Adolescence has a complete dynamic towards adulthood. ICBB Islamic Boarding School in facing the challenges of the alpha generation of students, namely; 1) Mission Crisis Youth; 2) Adolescents who do not know themselves, their roles and what their duties are; 3) the orderliness of Congregational Prayer Worship; 4) Trend and Youth Idol; 5) competent educators; 6) Emotional control; 7) Changes in community needs; 8) Fulfillment of Obligations on Property Issues.